Force in numbers: high-throughput screening approaches to unlock microbial transport. (April 2022) - Jenkins Sánchez, Liam Richard; Claus, Silke; Muth, Liv Teresa; Salvador López, José Manuel; Van Bogaert, Inge
Highlights: Transport is a vital research area for developing successful cell factories, yet challenging to study and engineer. Coupling transport to growth rates can provide high-throughput selection for some substrates. Synthetic biology tools such as biosensors enable efficient scanning of large libraries and variant isolation. Expanding the screening toolbox facilitates wide-scale transporter identification and optimization Graphical abstract: Abstract : Biological membranes are inherently complex, making transport processes in microbial cell factories a significant bottleneck. Lack of knowledge on transport proteins' characteristics and the need for advanced technical equipment often hamper transporter identification and optimization. For these reasons, moving away from individual characterization and towards high-throughput mining, engineering, and screening of transporters is an increasingly attractive approach. Superior transporters can be selected from large libraries by coupling their activity to growth, for substrates that function as feedstocks or toxic compounds. Other compounds can be screened thanks to recent advances in the design and deployment of synthetic genetic circuits (biosensors). Furthermore, novel strategies are rapidly increasing the repertoire of biomolecule transporters susceptible to high-throughput selection methods.